MIF functional polymorphisms are associated with acute GVHD progression and steroid-refractoriness - Aharon, Aviran; Avni, Batia; Louzoun, Daniel; Elias, Shlomo; Stepensky, Polina; Ram, Ron; Zuckerman, Tsila; Meza-Romero, Roberto; Vandenbark, Arthur A.; Grisariu, Sigal; Benedek, Gil (Frontiers in Immunology, 2025)
IntroductionApproximately 50% of allogeneic hematopoietic stem cell transplantation (HSCT) Q6 recipients develop graft versus host disease (GVHD). Glucocorticoids (GC) are the first line of treatment for both acute and chronic GVHD. Failure to respond to GC [steroid-refractory (SR)] encompasses a very poor outcome with high mortality. Macrophage migration inhibitory factor (MIF) is released during transplantation and triggers enhanced and prolonged immune reactions. Persistently elevated levels of MIF have been shown to override both endogenous and exogenous antiinflammatory effects of GC.MethodsTwo functional polymorphisms in the MIF gene, a −794 CATT5–8 microsatellite repeat and a −173 G/C single-nucleotide polymorphism, were analyzed in 86 patients who underwent allogeneic HSCT. We also measured MIF serum levels at different time points before and after HSCT.ResultsFrequencies of MIF high-expression -794 CATT7 containing genotypes were increased in patients with grade III-IV acute GVHD (aGVHD) (36.8%) compared with patients that did not develop aGVHD (5.8%) and patients with grade II aGVHD (0%), (p=0.0019, 0.0080 respectively). We also demonstrated that the frequencies of the MIF-794 CATT7 and -173 C containing genotypes, were significantly associated with steroid-refractory aGVHD (46.6%, 60% respectively) compared to steroid-responsive aGVHD (0%, 5.3% respectively), (p=0.0011, P=0.0007 respectively). We further showed that MIF circulating levels preceded onset of severe aGVHD.DiscussionOur findings suggest that genetically controlled high expression MIF genotypes are associated with aGVHD worsening and could serve as a biomarker enhancing identification and treatment of steroid-refractory disease.